Identifying the design and technical parameters of a mixing and dosing unit of the process of preparation of compound feeds with dispersing forced mixing - Mammadov, Gabil; Abdiyeva, Narmin; Saidov, Rasim; Hajiyev, Rovshan; Taghiyev, Urfan; Allahverdiyeva, Gahira; Imanova, Natavan; Aliyev, Bahruz; Iskenderova, Aynur (Eastern-European Journal of Enterprise Technologies, 2026)
The object of research in this study is a screw dispenser that dispenses dry, dispersed feed. The problem to be solved is this: when using dispensers of complex design, labor and material costs for their repair and maintenance increase, as well as the efficiency of their use decreases. When using the proposed model of a device for preparing mixed feed with a scattering force, it is possible to determine the following rational design modes and kinematic parameters: rotation speed of the screw of the mixing section ω = 4...12 s⁻1, number of blades 6...8, feed rate or component u = 0.005...0.045 m/s. Using a model of a device for preparing feed for forced mixing using appropriate methods and measurements, the following rational constructive, modal and kinematic parameters were determined: rotation speed of the screw of the mixing section ω = 4–12 s–1; number of blades 6...8 pcs.; feed rate or feed component v = 0.005...0.045 m/s. With the specified values of parameters, heterogeneity or uniformity of the feed mixture, the total required power, respectively, was: δ = 7...11; λ = 93...89%; N = 3.5...4.94 kW. The design features of the metering mixer, the parameters of the constructive mode of operation and practical recommendations for use, justified as a result of the study, are of practical importance for feed mills. The results and optimized values obtained during the dosing of feed material in the preparation of concentrated feed mixtures, in comparison with their continuous operation over time, are of theoretical importance for subject programs, scientific research and experimental design work on the preparation of feed mixtures